From tales of enchantment to tales of empowerment: Finding women's voices through fairy tale narratives. - Zigman, Jane. (University of Ottawa (Canada), 2000)
Research suggests that fairy tales permeate society and affect subjective identity through old and new versions that serve to domesticate desire. While some researchers suggest that fairy tales have negative effects on how women construct their lives, others claim that women resist or subvert their restrictive meanings and gender roles. From a cultural studies perspective, this case study investigates the perceived impact of fairy tales on subjectivity, as well as on past and present life choices. Feminist, poststructuralist, and psychoanalytic analyses uncover how subjective identities may be produced and resisted through cultural influences like fairy tales. Thematic analysis of group discussions and written responses by mature women show that fairy tales are instrumental in forming subjective identities and influencing the life choices of participants. The findings of this study indicate that some participants perceive fairy tales to be influential in constituting the life stories that they were able to imagine, while group discussions and written responses of other participants also demonstrate possible influences of fairy tales in their lives. This research may help educators understand how this process occurs in order to create programs that effectively resist or subvert messages internalized in this way.
Keywords: Folklore.